2014
DOI: 10.5253/078.101.0204
|View full text |Cite
|
Sign up to set email alerts
|

Tide Associated Incubation and Foraging Behaviour of Saunders's GullsLarus saundersi

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Additionally, adults may not be able to access prey items evenly throughout all periods of the day. For instance, Saunders's Gulls (Chroicocephalus saundersi), which feed on mudflats, have been found to increase incubation with higher sea levels regardless of time of day suggesting a tradeoff between incubation and temporal food availability (Yoon et al 2014).…”
mentioning
confidence: 99%
“…Additionally, adults may not be able to access prey items evenly throughout all periods of the day. For instance, Saunders's Gulls (Chroicocephalus saundersi), which feed on mudflats, have been found to increase incubation with higher sea levels regardless of time of day suggesting a tradeoff between incubation and temporal food availability (Yoon et al 2014).…”
mentioning
confidence: 99%
“…Avian predation in intertidal and shallow subtidal zones is reported to be influenced by the tidal level and tidal cycle (Dominguez, ; Matsunaga, ; Yoon, Yoon, Go, Joo, & Park, ). In the present study, no clear relationship was confirmed between the average tidal level and the predation rate by the gull on the abalone in the late afternoon when the predation by the gull on the abalone was most active.…”
Section: Discussionmentioning
confidence: 99%